Household Liquid Waste Adsorption With Mineral Magnetite (Fe3O4) - Hamdan, Abd Mujahid; Fajri, Wilda Nur; Rahmi, Rizna; Hanif, Hanif (Phi: Jurnal Pendidikan Fisika dan Terapan, 2022)
The increase in population in Indonesia will lead to increased household activities which are a source of environmental pollution. Household liquid waste in Lamglumpang Village, Ulee Kareng District, Banda Aceh City contains pollutant parameters that exceed quality standards based on COD, TSS, pH and turbidity parameters. Magnetite has the potential to be used as an adsorbent in domestic wastewater treatment. This study aims to determine the ability of magnetite adsorbent. Adsorption experiments were carried out with variations in magnetite mass of 1, 3 and 5 g and adsorption contact times of 6, 8 and 10 hours with a rotating speed of 150 rpm and without stirring. The results showed that the mass of the adsorbent, contact time and rotational speed affected the effectiveness of adsorption. Magnetite is effective in reducing COD levels reaching 90.96% at a mass variation of 5 grams with a contact time of 8 hours with a rotating speed of 150 rpm, TSS reaching 94.51% at a mass variation of 1 gram with a contact time of 10 hours with a rotating speed of 150 rpm, pH reached 30.88% in a mass variation of 3 grams with 5 grams and a contact time of 10 hours with a rotational speed of 150 rpm and turbidity reached 90.39% in a mass variation of 1 gram with a contact time of 10 hours with a rotational speed of 150 rpm. These results indicate that magnetite has the potential to be used in domestic wastewater treatment.